An oxygen‐releasing tablet to reduce the hypoxia‐induced damage of Chinese mitten crabs (Eriocheir sinensis). Issue 12 (14th November 2021) - Wang, Fenfen; Nian, Linyu; Wang, Mengjun; Xie, Yao; Yuan, Biao; Cheng, Shujie; Cao, Chongjiang
Abstract: Hypoxia is one of the main factors causing the quality deterioration of Chinese mitten crab ( Eriocheir sinensis ) during transportation. Therefore, developing an oxygen‐releasing material is essential in the transportation of E. sinensis . Herein, a sustained‐release oxygen tablet based on polylactic acid and calcium peroxide was developed by phase separation and tablet pressing techniques, which showed the oxygen could release up to 7 days and the content was 17.99%. Subsequently, a 6‐day storage experiment was conducted to evaluate the effects of the oxygen‐releasing tablet (ORT) on antioxidant capacity and respiratory metabolism level of E. sinensis . The results proved that ORT could delay the oxidative stress reaction, effectively avoid oxidative damage, and improve the aerobic respiration ratio of E. sinensis . Hence, this work develops the ORT as a novel platform for application in the transportation of crustacean aquatic products, which cannot only maintain their quality but also bring enormous economic value. Novelty impact statement: A novel ORT was synthesized, which could release oxygen up to 7 days and the content was 17.99%. In addition, the ORT could delay the oxidative stress reaction, effectively avoid oxidative damage, and improve the aerobic respiration ratio of E. sinensis .